ANALISIS UNJUK KERJA DARI KOMPONEN â KOMPONEN UTAMA PEMBANGKIT LISTRIK TENAGA UAP (PLTU) DI TAMBANG BATU BARA, PT KALTIM PRIMA COAL (KPC) - , FAJAR BANGKIT PRASETYO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Steam power plant that uses coal as fuel is widely used in Indonesia. This system uses the Rankine cycle which makes high-pressure steam as the primary energy source. With the increasing electricity consumption, the efficiency of the generation system needs to be improved. Analysis of performance of main components of the power plant needs to be done to determine the efficiency of the system and to determine factors that can affect the efficiency, so that efficiency can be improved. The main components of this power plant is feedwater pump, boiler, steam turbine, and turbine condenser . The study was conducted in Tanjung Bara power plant owned by PT Kaltim Prima Coal (KPC), in the province of Kalimantan Timur. Analysis of performamce of pumps by using the Bernoulli equation, boilers with a direct method/ output - input and an indirect method in according to USA Standard AMSE PTC - 4-1 Power Test Code Steam Generating Units, steam turbines by using the unjuk kerja equation, and condenser with LMTD and Îµ - NTU methods. From the analysis of the data, obtained an average efficiency of 53 % pump, boiler efficiency with direct method is 42.65 % and indirect method is 88.78 %, the average efficiency of the steam turbine is 74.002 %, and with the LMTD method, the average heat transfer coefficient of the condenser to inner diameter of the pipe Ui is 3018.8 W/(m 2 . o C) and the outside diameter of the pipe Uo is 2822.3 W/(m 2 . o C) and with the Îµ-NTU method, the average heat transfer coefficient of the condenser to inner diameter of the pipe Ui is 3598.4 W/(m 2 . o C) and the outside diameter of the pipe Uo is 3364.2 W/(m 2 . o C).